2012
DOI: 10.1177/0267658311423455
|View full text |Cite
|
Sign up to set email alerts
|

Direct mapping of acoustics to phonology: On the lexical encoding of front rounded vowels in L1 English– L2 French acquisition

Abstract: It is well known that adult US-English-speaking learners of French experience difficulties acquiring high /y/–/u/ and mid /œ/–/ɔ/ front vs. back rounded vowel contrasts in French. This study examines the acquisition of these French vowel contrasts at two levels: phonetic categorization and lexical representations. An ABX categorization task (for details, see Section IV) revealed that both advanced and intermediate learners categorized /œ/ vs. /ɔ/ and /y/ vs. /u/ differently from native speakers of French, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 80 publications
(150 reference statements)
4
60
1
Order By: Relevance
“…In order to explain this finding, it is plausible to claim that L1 phonological representations might have been activated already in the immediate imitation condition independently from the necessesity of their activation. This claim is supported by studies that show that auditory information may directly co-activate L1 phonological representations [40,41]. Another piece of evidence that supports this claim is also found in my previous work [18], in which reaction times in discrimination tasks were longer for learners than non-learners.…”
Section: Discussionsupporting
confidence: 72%
“…In order to explain this finding, it is plausible to claim that L1 phonological representations might have been activated already in the immediate imitation condition independently from the necessesity of their activation. This claim is supported by studies that show that auditory information may directly co-activate L1 phonological representations [40,41]. Another piece of evidence that supports this claim is also found in my previous work [18], in which reaction times in discrimination tasks were longer for learners than non-learners.…”
Section: Discussionsupporting
confidence: 72%
“…There is a body of literature, however, that has challenged the assumption that phonetic distinctions must precede phonological encoding in the lexicon. These studies have shown that L2 leaners may establish lexical contrasts but still exhibit persistent perceptual errors in the discrimination of phonemic contrasts in categorization tasks (Cutler, Weber, & Otake, 2006; Darcy et al, 2012; Escudero, Hayes-Harb, & Mitterer, 2008; Hayes-Harb & Masuda, 2008; Weber & Cutler, 2004). The fact that advanced L2 learners may acquire knowledge of lexical contrasts despite unreliable performance on discrimination tasks confirms that the establishment of a lexical contrast is independent of the acquisition of phonetic categories.…”
Section: Discussionmentioning
confidence: 99%
“…Broersma, 2012;Cutler et al, 2006;Darcy et al, 2012;Weber and Cutler, 2004). Furthermore, L1 homophone effects observed for orthographic stimuli (Ota et al, 2009) suggest that L1 homophone effects can manifest themselves without the direct involvement of phonetic processing, raising two possibilities: (1) L1 homophone effects can occur independently of L2 listeners' abilities to distinguish difficult L2 contrasts, or (2) the effects can occur under an indirect influence of L2 listeners' lack of abilities to discriminate difficult L2 contrasts reliably.…”
Section: Discussionmentioning
confidence: 99%